2007
DOI: 10.1007/s10295-007-0259-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of homoserine dehydrogenase gene and its effect on cephamycin C production in Streptomyces clavuligerus

Abstract: The aspartate pathway of Streptomyces clavuligerus is an important primary metabolic pathway which provides substrates for beta-lactam synthesis. In this study, the hom gene which encodes homoserine dehydrogenase was cloned from the cephamycin C producer S. clavuligerus NRRL 3585 and characterized. The fully sequenced open reading frame encodes 433 amino acids with a deduced M (r) of 44.9 kDa. The gene was heterologously expressed in the auxotroph mutant Escherichia coli CGSC 5075 and the recombinant protein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Induction of metL gene in P. temperata , which is known to be responsible for the synthesis of homoserine which serves as a precursor to threonine, lysine and methionine, reflects a growth-limiting concentration of these amino acids or an enhanced need for homoserine in the nematode as has been noted in Salmonella during infection of pigs [14]. Disruption of metL results in an increase in intracellular free lysine concentration during stationary phase in Streptomyces clavuligerus [15]. The fact that metL mutant supported nematode reproduction but had reduced persistence in the infective juveniles suggests that lysine may be helpful to H. bacteriophora growth and homoserine may be needed for P. temperata survival in the nematode.…”
Section: Discussionmentioning
confidence: 93%
“…Induction of metL gene in P. temperata , which is known to be responsible for the synthesis of homoserine which serves as a precursor to threonine, lysine and methionine, reflects a growth-limiting concentration of these amino acids or an enhanced need for homoserine in the nematode as has been noted in Salmonella during infection of pigs [14]. Disruption of metL results in an increase in intracellular free lysine concentration during stationary phase in Streptomyces clavuligerus [15]. The fact that metL mutant supported nematode reproduction but had reduced persistence in the infective juveniles suggests that lysine may be helpful to H. bacteriophora growth and homoserine may be needed for P. temperata survival in the nematode.…”
Section: Discussionmentioning
confidence: 93%
“…In our previous study, the growth of the AK39 strain was rather poor in chemically-defined medium, CDM, in spite of a two-fold increased specific level of cephamycin C. 17 Some inhibitory effects of glycerol on cephamycin C production 18,19 as well as improvement of growth and cephamycin C yields by L-asparagine 20,21 have been previously reported. In the present study, the composition of CDM was submitted to several modifications to improve the growth of this strain and their transformants.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were grown in mCDM, and samples were collected at intervals during cultivation. Intracellular free amino acids were extracted as described by Yılmaz et al 17 Following automated pre-column derivatization with o-phthaladehyde (OPA), amino acid analysis was performed by conventional reverse-phase Growth determination. Cultural growth was determined by DNA quantification with diphenylamine method adapted from Burton.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By investigating the feedback of aspartate kinase, Hamano et al obtained a high-yield ε-PL producing strain (M68V) (Hamano et al 2007). By knocking out the homoserine dehydrogenase gene in Streptomyces clavuligerus, Yilmaz et al obtained a mutagenized strain with a 4.3-fold ε-PL yield compared with the original strain (Yılmaz et al 2008). Vanooyen et al found that reducing the activity of citrate synthase can buffer the increase of the substrate and thus obtained a high-yield lysine producing strain of Corynebacterium glutamicum (Vanooyen et al 2012).…”
Section: )mentioning
confidence: 99%